Circular Economy in Indonesian MSMEs: A Qualitative Study on The Role of Eco-Innovation and Sustainable Supply Chains - Ani Mekaniwati; Aang Munawar; Bambang Hengky Rainanto; Dwi Maulina (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Indonesia’s transition toward a circular economy is increasingly urgent due to rising waste from urbanization and industrial growth. Although MSMEs contribute significantly to GDP, low resource efficiency and fragmented supply chains make them major waste contributors.Purpose: This study examines how the synergy between ecological innovation (eco-innovation) and Sustainable Supply Chain Management (SSCM) enhances the effectiveness of circular economy implementation in Indonesian MSMEs.Design/methodology/approach: An exploratory qualitative approach was employed through Focus Group Discussions (FGDs) involving MSMEs, associations, local governments, and experts in West Java and Bengkulu. Data were analyzed using NVivo 15 with thematic coding, heatmaps, and concept mapping.Findings/Results: The findings indicate that circular economy implementation in MSMEs is driven by the synergy of eco-innovation and SSCM through collaboration, information sharing, training, and stakeholder engagement. However, it is constrained by limited green financing, human resources, and institutional support, with regional differences shaping economic and environmental outcomes.Conclusion: MSMEs play a strategic role in advancing the circular economy but require localized policy support, digital innovation, and long-term partnerships.Originality/value (State of the art): This study provides novel empirical evidence on the synergy of eco-innovation and SSCM at the MSME level in developing countries. Keywords: circular economy, ecological innovation, MSMEs, green financing, sustainable supply chain